Inability to Trust People in The Novel The Leavers by Lisa Ko - Ardi Oromahi; Kurnia Ningsih (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of inability to trust people which is done by an immigrant child who was separated multiple times from his family. The purpose of this study is to know the contribution of character, plot (conflict), and setting in revealing the inability to trust people. This analysis is related to the concept of neurosis by Sigmund Freud and Psychosocial Development by Erik Erikson that is supported by the text and context based interpretation. The result of this analysis shows the protagonist suffers from social relationship and mental problem that can be seen from his attitude and behavior.